Novelty, Distinctiveness, Uniformity, and Stability Testing for Three Potential Lines of Black Rice - Nandariyah - Nandariyah; Yuyun Nitasari; Bambang Pujiasmanto; Endang Yuniastuti (Journal of Biodiversity and Biotechnology, 2023)
Black rice Cempo Ireng is a local variety with a long plant life, high plant posture, and low productivity. Plant breeding by gamma irradiation was carried out to correct these weaknesses. The results of the gamma irradiation process included a selection process for each generation and produced potential lines numbers such as 8, 51, and 52. The characterization was based on the NDUS (Novelty, Distinctiveness, Uniformity, and Stability) test. The purpose of this study was to characterize potential lines as one of the requirements for the release of plant varieties. The study was conducted in the paddy fields of Pakahan Village, Jogonalan District, Klaten Regency, from February-July 2022. The method used was a single factor randomized complete block design with three replications. Data were analyzed by T test with 5% level. The results of the study showed that the three potential lines have differences with the parent and the Sembada varieties. Three potential lines can be deemed to be new, dictinct, uniform, and stable.